Cardiovascular and Metabolic Effects of ANGPTL3 Antisense Oligonucleotides - Graham, Mark J; Lee, Richard G; Brandt, Teresa A; Tai, Li-Jung; Fu, Wuxia; Peralta, Raechel; Yu, Rosie; Hurh, Eunju; Paz, Erika; McEvoy, Bradley W; Baker, Brenda F; Pham, Nguyen C; et al. (The New England journal of medicine, 2017)
Angiopoietin-like 3 (ANGPTL3) inhibits endothelial lipase and lipoprotein lipase. Injection of antisense oligonucleotides targeting ANGPTL3 messenger RNA effects a reduction of atherogenic lipoproteins in humans and mice and a slowing of progression of atherosclerosis in mice.